A method for preparing lithium manganese iron phosphate positive electrode material

Through homogeneous system reaction and specific raw material ratio, the problem of ferromanganese ferromanganese phosphate segregation during the preparation process is solved, and the homogeneous synthesis and electrochemical performance of the material are improved.

CN118145615BActive Publication Date: 2025-02-28YIBIN TIANYUAN NEW LITHIUM BATTERY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410150872.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-02
Publication Date
2025-02-28
Estimated Expiration
2044-02-02

AI Technical Summary

Technical Problem

In the prior art, lithium manganese iron phosphate positive electrode material is prone to ferromanganese segregation during the preparation process, resulting in manganese dissolution and affecting the circulation life of the material.

Method used

Using a homogeneous system reaction, granulation and sintering are prepared by mixing lithium sources, phosphorus sources, carbon sources, iron sources and manganese sources, and manganese sources are selected as the iron source and manganese source. Deionized water is used as the solvent, and then mixed with manganese ferrocyanide, and other raw materials are added. Through spray drying granulation and high-temperature sintering, lithium manganese phosphate positive electrode material with excellent electrical properties is formed.

Benefits of technology

The problem of ferromanganese segregation was effectively overcome, and homogeneous synthesis of lithium manganese iron phosphate positive electrode material was achieved, which improved the electrochemical performance and cycle life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118145615B_ABST
    Figure CN118145615B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a lithium iron manganese phosphate positive electrode material, which comprises mixing a lithium source, a phosphorus source, a carbon source, an iron source and a manganese source, and then granulating and sintering the mixture, wherein the iron source and the manganese source are from manganese ferrocyanide; the manganese ferrocyanide is a manganese cyanide solution with a mass concentration of 30% to 40%, and the solvent is deionized water. The invention takes a different approach, and the unique manganese-iron ratio (Mn:Fe=3:2) of manganese ferrocyanide just meets the optimal ratio design of lithium iron manganese phosphate (LiMn 0.6 Fe 0.4 PO4), directly mix manganese ferrocyanide with a phosphorus source, a lithium source, a carbon source, etc., grind them into a uniform dispersion, use spray drying to achieve uniform mixing of solid materials, and then form a lithium ion battery positive electrode material with excellent electrical properties after high-temperature sintering and pulverization. The present invention overcomes the problem that manganese iron phosphate cannot be precipitated in proportion at the same time under the conventional phosphate precursor process, effectively realizes the mixing of manganese and iron atoms, and does not cause manganese segregation and manganese dissolution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a positive electrode material, in particular to a method for preparing a lithium manganese iron phosphate positive electrode material. Background Art

[0002] At present, the cathode materials of lithium-ion batteries are mainly lithium cobalt oxide (LCO), ternary materials (NCM) and lithium iron phosphate (LFP). In the past one or two years, with the increase of electric vehicles and the gradual expansion of energy storage, people's attention to battery safety has also gradually increased. In addition to the improvement of battery design technology (such as BYD's blade battery, CATL's CTP technology, etc.), the research and development of new materials is also particularly critical. LFP has gradually become the main cathode material for electric vehicles or energy storage batteries due to its high safety, but for LFP batteries, the development of its energy density has almost reached its limit, and there is not much room for performance improvement. The crystal structure of lithium manganese iron phosphate (LMFP) is similar to that of LFP, and it also has the characteristics of stable chemical properties and excellent safety performance. At the same time, the manganese element doped in LMFP can increase the charging voltage of the material, increasing the charging voltage from 3.4V of LFP to 4.1V, which increases the theoretical energy density of LMFP batteries by 15-20%, further expanding the driving range. LMFP has better safety performance than NCM and higher energy density than LFP. In addition, LMFP has low dependence on rare metals and can be produced on the same line as LFP, which has obvious cost advantages. Like LFP, LMFP also has an olivine structure, in which the PO4 tetrahedron is very stable and can play a structural support role during the charge and discharge process, thus giving LMFP excellent thermodynamic and kinetic stability. In addition, LMFP has a wide range of raw materials, is environmentally friendly, and has a high theoretical specific capacity (170mAh / g). Due to the Mn in LMFP, the LMFP has a high thermal conductivity and a high thermal conductivity. 2+ / Mn 3+ The corresponding 4.1V redox platform is 0.7V higher than the LFP platform (3.4V). When the other designs of the batteries assembled with the two materials are the same, the battery energy density corresponding to LMFP can be increased by 21% compared with LFP.

[0003] Lithium iron manganese phosphate (LMFP), general formula is LiMn x Fe 1-x PO4, lithium iron manganese phosphate and lithium iron phosphate are basically the same in terms of synthesis method. The main methods in industry are high temperature solid phase method, hydrothermal synthesis method, co-precipitation method, etc. Among them, the common co-precipitation method is to mix appropriate raw materials, such as soluble ferrous salt, manganese salt, lithium salt, phosphate, etc., and add a precipitant to generate a precipitate. The generated precipitate is dried, calcined, etc. to obtain an iron-manganese-containing precursor, which is then carbon-coated to improve its electrochemical performance, forming a carbon-coated manganese iron manganese lithium phosphate positive electrode material.

[0004] In Chinese patent CN111900344A, a transition metal salt solution A, a phosphorus solution B and an ammonia solution C are added dropwise to a reactor at a molar ratio of Mn and Fe to prepare a lithium iron manganese phosphate positive electrode material precursor; the precursor is then prepared with a lithium source according to a molar ratio, and a coated carbon source and a doped metal compound are added, and calcined under an inert atmosphere to obtain a carbon-coated lithium iron manganese phosphate positive electrode material, wherein deionized water is used as a solvent, a divalent manganese source compound and a divalent iron source compound are prepared according to the chemical formula LiMn x Fe 1-x The atomic ratio of Mn and Fe in PO4 is configured with transition metal ion salt solution A, wherein 0≤x≤1; the divalent manganese source compound is one or more of MnCl2, Mn(NO3)2, MnSO4 and (CH3COO)2Mn, the divalent iron source compound is one or more of FeCl2, Fe(NO3)2, FeSO4 and (CH3COO)2Fe, and the metal ion concentration is 1.0-3.0 mol / L. However, because the solubility product constants of iron and manganese phosphates are inconsistent, the lithium manganese iron phosphate synthesized from the two precursors is prone to iron and manganese inhomogeneity, and iron and manganese segregation is prone to occur. Manganese segregation will lead to the Jan-Taylor effect of manganese ions, accelerate manganese dissolution, deposit on the surface of the negative electrode, destroy the SEI film, and ultimately affect the cycle life of the positive electrode material.

[0005] Chinese patent CN116692814A discloses a lithium iron manganese phosphate composite material and its preparation method and application. The preparation method of the lithium iron manganese phosphate composite material of the invention includes: 1) mixing polyvinyl pyrrolidone, manganese source, iron source and solvent to obtain a metal ion solution; 2) mixing the metal ion solution and potassium ferrocyanide solution, and obtaining a Prussian blue precursor through a coprecipitation reaction; 3) mixing the Prussian blue precursor, phosphorus source and lithium source, and then pre-calcining and calcining to obtain the lithium iron manganese phosphate composite material. The invention is designed to first synthesize a Prussian blue precursor with uniform metal element distribution and core-shell structure, namely, ferromanganese ferrocyanide, by a coprecipitation method. The Prussian blue analog is a class of compounds containing cyano and transition metal ions, and its molecular formula can be expressed as M[Fe(CN)6]; then, after the Prussian blue precursor is fully mixed with the Li source and the P source, the lithium iron manganese phosphate composite material with holes is synthesized by a solid sintering method. Both the Prussian blue precursor and the lithium iron manganese phosphate are spherical. The method synthesizes lithium manganese iron phosphate composite material (i.e. LiMn) with cavities by solid-state sintering. x Fe 1-xPO4 / NC positive electrode material, and 0.2≤x≤0.4). However, in order to solve the problem of uneven element distribution in lithium iron manganese phosphate and improve its electrochemical performance, the method discloses a method of synthesizing a Prussian blue precursor (ferromanganese ferrocyanide) with uniform metal element distribution by coprecipitation, and then mixing a lithium source and a phosphorus source to obtain a lithium iron manganese phosphate material. The method controls the amount of raw materials, the mixing method and the calcination conditions so that the metal can qualitatively move to the outside to form a lithium iron manganese phosphate composite material with a loose porous structure, a stable internal hole structure, and an external structure composed of fine nanoparticles and a nitrogen-doped carbon layer. However, the method introduces impurities K, which are generally cationic impurities and cannot be directly used in the preparation of lithium battery materials. It needs to be removed, and it is necessary to control K and Na below 200ppm so as not to affect the performance of lithium batteries. It is usually further removed by various ion exchange resins or various reagents, resulting in a complicated process and poor controllability. Secondly, the LiMn 0.25 Fe 0.75 PO4 manganese only replaces 25% of iron. Theoretically, the discharge voltage will not increase much. In the composite material formed by it, manganese is lower than iron, so it cannot be called high manganese, and it is not easy to form manganese dissolution phenomenon. In addition, because it forms a core-shell structure, although iron on the surface is conducive to conductivity, it also proves that the system is inhomogeneous.

[0006] Obviously, in the prior art, in the preparation process of lithium manganese iron phosphate, the manganese source and the iron source are configured according to the required manganese-iron ratio. In the process of forming the precursor, especially the configuration of the high manganese series, it is easy for the manganese and iron phosphates to be inconsistent due to the volume constant, making the system inhomogeneous, resulting in manganese segregation and manganese dissolution. How to overcome such defects has become an urgent problem to be solved in the current preparation process of LMFP. Summary of the invention

[0007] The purpose of the present invention is to overcome the problem of manganese-iron segregation and manganese dissolution caused by the large solubility product difference between manganese and iron phosphates in the prior art, and to prepare a lithium manganese iron phosphate precursor with stable and excellent electrical properties by adopting a homogeneous system reaction, and to make the preparation process simple and controllable.

[0008] The technical solution adopted by the present invention to solve its technical problem is:

[0009] A method for preparing lithium manganese iron phosphate positive electrode material is to mix a lithium source, a phosphorus source, a carbon source, an iron source and a manganese source, and then granulate and sinter the mixture, wherein the iron source and the manganese source come from manganese ferrocyanide; the manganese ferrocyanide is a manganese cyanide solution with a mass concentration of 30% to 40%, and the solvent is deionized water.

[0010] The lithium source and phosphorus source are selected from lithium dihydrogen phosphate, lithium carbonate and a mixture of ammonium dihydrogen phosphate; the carbon source is selected from one or more of acetylene black, carbon nanotubes, and carbon black in inorganic carbon, or one or more of sucrose, glucose, citric acid, and ascorbic acid in organic carbon.

[0011] The method for preparing lithium manganese iron phosphate positive electrode material is prepared according to the following steps:

[0012] S1: using deionized water as a solvent and mixing it with manganese ferrocyanide to obtain a mixture I, wherein the mixture I is a manganese ferrocyanide solution with a mass concentration of 30% to 40%;

[0013] S2: adding a lithium source, a phosphorus source and a carbon source to the mixture I to obtain a mixture II, wherein the ratio of lithium atoms to the total atoms of iron and manganese in the mixture II is 1.03-1.05:1, the ratio of phosphorus to lithium is 1:1, and the amount of carbon source added is 8-10% of the total mass of lithium iron manganese phosphate;

[0014] S3: Granulate the mixture II to obtain spray-dried granulated particles, wherein the drying air inlet temperature is 240-260° C., the air outlet temperature is 70--90° C., and the particle size of the particles after granulation is 10-30 μm.

[0015] S4: Sintering the particles at high temperature to obtain LiMn 0.6 Fe 0.4 PO4, wherein the sintering temperature is 720-760°C and the holding time is 8-12 hours.

[0016] S5: The sintered material is subjected to air flow pulverization to obtain the finished product LiMn 0.6 Fe 0.4 PO4 positive electrode material, wherein D50 is 2-5 μm, wherein the crushing parameters are gas source pressure of 0.55-0.65 MPa, feeding frequency of 36-46 Hz, and classifying wheel frequency of 42-45 Hz.

[0017] The present invention selects manganese ferrocyanide as an iron source and a manganese source, uses deionized water as a solvent, mixes with manganese ferrocyanide, and then adds a lithium source, a phosphorus source and a carbon source, and granulates after mixing to obtain spray-dried granulated particles, and then sintering at a high temperature to obtain lithium manganese iron phosphate material. Since the chemical formula of manganese ferrocyanide is Mn3[Fe(CN)6]2·xH2O, according to the results of coordination field theory and spectral measurement, CN - It is a strong field ligand with strong coordination effect, especially with transition metal ions, it can form a series of coordination compounds, such as red blood salt K3[Fe(CN)6], yellow blood salt K4[Fe(CN)6]·3H2O, Prussian blue Fe4[Fe(CN)6]3, etc., which are all based on Fe 2+ or Fe 3+The current research shows that in Prussian blue, Fe 2+ or Fe 3+ There is no essential difference, both are [Fe(CN)6] 3- or [Fe(CN)6] 4- exists in the form of.

[0018] Similarly, [Fe(CN)6] 3- or [Fe(CN)6] 4- Based on Mn 2+ / Co 2+ The formation of more Prussian blue compounds, among which manganese ferrocyanide Mn3[Fe(CN)6]2 is based on Mn 2+ and Fe 3+ The present invention takes a different approach and uses the unique manganese-iron ratio (Mn:Fe=3:2) of manganese ferrocyanide to exactly meet the optimal ratio design of lithium manganese iron phosphate (LiMn 0.6 Fe 0.4 PO4), directly mix manganese ferrocyanide with phosphorus source, lithium source, carbon source, etc., grind into a uniform dispersion, use spray drying to achieve uniform mixing of solid materials, and then form a lithium-ion battery positive electrode material with excellent electrical properties after high-temperature sintering and pulverization. This technical solution overcomes the problem that manganese iron phosphate cannot be precipitated in proportion at the same time under the conventional phosphate precursor process, and effectively achieves the mixing of manganese and iron atoms, that is, there will be no manganese segregation and manganese dissolution;

[0019] In addition, the present invention selects Mn3[Fe(CN)6]2 as the iron source and manganese source, mixes it with a phosphorus source, a lithium source, a carbon source, etc., and grinds it to obtain a uniform dispersion system. Figure 1 The LiMn prepared by the method of the present invention is shown 0.6 Fe 0.4 From the XRD diagram of the PO4 product, it can be found that the prepared product presents a single homogeneous structure, and there is no mixed phase of lithium manganese phosphate and lithium iron phosphate due to the segregation of manganese. At the same time, the EDS diagram of the product shows that the atomic distribution of manganese and iron is consistent, which further verifies that the method of the present invention can synthesize homogeneous lithium manganese iron phosphate materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 LiMn prepared in Example 1 of the present invention 0.6 Fe 0.4 XRD pattern of PO4 product;

[0021] Figure 2 LiMn prepared in Example 1 of the present invention 0.6 Fe 0.4EDS diagram of PO4 product;

[0022] Figure 3 LiMn prepared in Comparative Example 1 of the present invention 0.6 Fe 0.4 EDS diagram of PO4 product;

[0023] Figure 4 LiMn prepared in Example 1 of the present invention 0.6 Fe 0.4 SEM image of PO4 product;

[0024] Figure 5 LiMn prepared in Comparative Example 1 of the present invention 0.6 Fe 0.4 SEM image of PO4 product. DETAILED DESCRIPTION

[0025] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0026] Embodiment 1:

[0027] Preparation of LiMn 0.6 Fe 0.4 The method of PO4 positive electrode material is prepared according to the following steps:

[0028] S1: using deionized water as a solvent and mixing it with manganese ferrocyanide to obtain a mixture I, wherein the mixture I is a manganese ferrocyanide solution with a mass concentration of 30%;

[0029] S2: adding lithium dihydrogen phosphate + sucrose to the mixture I to obtain a mixture II, wherein the ratio of lithium atoms to the sum of iron and manganese atoms in the mixture II is 1.05:1, the ratio of phosphorus to lithium is 1:1, and the amount of sucrose added is 8% of the total mass of lithium iron manganese phosphate;

[0030] S3: Granulating the mixture II to obtain spray-dried granulated particles, wherein the drying air inlet temperature is 240° C., the air outlet temperature is 70° C., and the particle size of the granulated particles is 30 μm;

[0031] S4: Sintering the particles at high temperature to obtain LiMn 0.6 Fe 0.4 PO4, where the sintering temperature is 720°C and the holding time is 12 hours;

[0032] S5: The sintered material is subjected to air flow pulverization, and the pulverizing parameters are air source pressure of 0.65Mpa, feeding frequency of 46Hz, and classifying wheel frequency of 45Hz to obtain the finished product LiMn 0.6 Fe 0.4 PO4, where D50 is 2.6 μm.

[0033] Test the finished product, such as Figure 1 XRD patterns and Figure 2 The EDS diagram of Figure 4 From the SEM image, it can be seen that the iron and manganese elements show a highly consistent distribution trend in the sample, indicating that this method can effectively achieve the uniform synthesis of lithium manganese iron phosphate materials. In addition, the primary particle size prepared by this method is very small, with an average size of only 150nm, which is conducive to shortening the diffusion distance of lithium ions and improving the release efficiency of lithium ions.

[0034] Embodiment 2:

[0035] Preparation of LiMn 0.6 Fe 0.4 The method of PO4 positive electrode material is prepared according to the following steps:

[0036] S1: using deionized water as a solvent and mixing it with manganese ferrocyanide to obtain a mixture I, wherein the mixture I is a manganese ferrocyanide solution with a mass concentration of 40%;

[0037] S2: adding lithium carbonate, phosphoric acid and glucose monohydrate to the mixture I to obtain a mixture II, wherein the ratio of lithium atoms to the sum of iron and manganese atoms in the mixture II is 1.04:1, the ratio of phosphorus to lithium is 1:1, and the amount of carbon source added is 10% of the total mass of lithium iron manganese phosphate;

[0038] S3: Granulating the mixture II to obtain spray-dried granulated particles, wherein the drying air inlet temperature is 260° C., the air outlet temperature is 90° C., and the particle size of the granulated particles is 10 μm;

[0039] S4: Sintering the particles at high temperature to obtain LiMn 0.6 Fe 0.4 PO4, where the sintering temperature is 760°C and the holding time is 8 hours;

[0040] S5: The sintered material is subjected to air flow pulverization, and the pulverizing parameters are air source pressure of 0.55Mpa, feeding frequency of 43Hz, and classification wheel frequency of 42Hz, to obtain the finished product LiMn 0.6 Fe 0.4 PO4, where D50 is 2 μm.

[0041] The finished product was tested, and the conclusion was basically consistent with that in Example 1.

[0042] Embodiment 3:

[0043] Preparation of LiMn 0.6 Fe 0.4 The method of PO4 positive electrode material is prepared according to the following steps:

[0044] S1: using deionized water as a solvent and mixing it with manganese ferrocyanide to obtain a mixture I, wherein the mixture I is a manganese ferrocyanide solution with a mass concentration of 36%;

[0045] S2: adding lithium carbonate, phosphoric acid and glucose monohydrate to the mixture I to obtain a mixture II, wherein the ratio of lithium atoms to the sum of iron and manganese atoms in the mixture II is 1.03:1, the ratio of phosphorus to lithium is 1:1, and the amount of carbon source added is 9% of the total mass of lithium iron manganese phosphate;

[0046] S3: Granulating the mixture II to obtain spray-dried granulated particles, wherein the drying air inlet temperature is 250° C., the air outlet temperature is 80° C., and the particle size of the granulated particles is 25 μm;

[0047] S4: Sintering the particles at high temperature to obtain LiMn 0.6 Fe 0.4 PO4, where the sintering temperature is 740°C and the holding time is 9 hours;

[0048] S5: The sintered material is subjected to air flow pulverization, and the pulverizing parameters are air source pressure of 0.55Mpa, feeding frequency of 36Hz, and classification wheel frequency of 42Hz, to obtain the finished product LiMn 0.6 Fe 0.4 PO4, where D50 is 4 μm.

[0049] The finished product was tested, and the conclusion was basically consistent with that in Example 1.

[0050] Comparative Example 1:

[0051] Preparation of LiMn 0.6 Fe 0.4 The method of PO4 positive electrode material is prepared according to the following steps:

[0052] S1: mixing iron oxide and manganese carbonate in a molar ratio of 4:6 to form a mixture I;

[0053] S2: adding lithium dihydrogen phosphate and sucrose to the mixture I to obtain a mixture II, wherein the ratio of lithium atoms to the total atoms of iron and manganese in the mixture II is 1.05:1, and the amount of sucrose added is 10% of the total mass of lithium iron manganese phosphate, and the mixture II is stirred at a high speed of 150 rpm for 5 minutes;

[0054] S3: Sintering the mixture II at high temperature to obtain sintered material LiMn 0.6 Fe 0.4 PO4, wherein the sintering temperature is 720°C and the holding time is 12 hours.

[0055] S4: The sintered material is subjected to air flow pulverization, and the pulverizing parameters are air source pressure of 0.65Mpa, feeding frequency of 46Hz, and classifying wheel frequency of 45Hz to obtain the finished product LiMn 0.6 Fe 0.4 PO4, where D50 is 4.2 μm.

[0056] Test the finished product, such as Figure 3 The EDS diagram of Figure 5 From the SEM image, it can be seen that the distribution of manganese and iron elements in the products synthesized by this method is inconsistent. It is likely that the segregation of manganese and iron has accelerated the dissolution of manganese, resulting in the synthesis of heterogeneous lithium manganese iron phosphate. In addition, the primary particles synthesized by this method are relatively large, the lithium ion diffusion path is long, and the capacity cannot be effectively released.

[0057] Comparative Example 2:

[0058] Preparation of LiMn 0.6 Fe 0.4 The method of PO4 positive electrode material is prepared according to the following steps:

[0059] S1: mixing ferrous oxalate and manganous oxide in a molar ratio of 4:6 to obtain a mixture I;

[0060] S2: adding lithium carbonate, phosphoric acid and glucose monohydrate to the mixture I to obtain a mixture II, wherein the ratio of lithium atoms to the total atoms of iron and manganese in the mixture II is 1.05:1, the molar ratio of lithium atoms to phosphorus atoms is 1:1, and the amount of glucose monohydrate added is 8% of the total mass of lithium iron manganese phosphate, and the mixture II is stirred at a high speed of 150 rpm for 5 minutes;

[0061] S3: sintering the mixture II at high temperature to obtain a sintered material LiMn0.6Fe0.4PO4, wherein the sintering temperature is 760° C. and the heat preservation time is 8 hours.

[0062] S4: The sintered material is subjected to air flow pulverization, and the pulverizing parameters are air source pressure of 0.55Mpa, feeding frequency of 43Hz, and classifying wheel frequency of 42Hz to obtain the finished product LiMn 0.6 Fe 0.4 PO4, where D50 is 4.2 μm.

[0063] The finished product was tested, and the conclusion was basically consistent with that of Comparative Example 1.

[0064] Power-off test method:

[0065] The positive electrode material A1 of Example 1, the positive electrode material A2 of Example 2, the positive electrode material A3 of Example 3, the positive electrode material B1 of Comparative Example 1, and the positive electrode material B2 of Comparative Example 2 are mixed with a conductive agent, a dispersant, etc. according to a certain mass, and the mixing ratio is SP: PVDF: active material = 5: 5: 90. After mixing evenly, it is a coatable material.

[0066] The material is applied to the positive electrode to produce a compaction density of 2.0 to 2.2 g / cm 3 The positive electrode was cut into a 12 mm diameter disc. The metal lithium sheet was used as the negative electrode and assembled into a CR2430 button cell in a glove box after drying.

[0067] Cycle performance test: LiPF6 is used as the solute, EC∶DEC∶DMC=1∶1∶1V% mixed solution is used as the solvent to make a 1M electrolyte, and the button battery is charged and discharged once at 0.1C, 0.33C, 0.5C and 1C rates in turn for activation. Finally, it is cycled 100 times at 0.1C and 1C rates respectively. It should be noted that the charging is carried out in a constant current and constant voltage mode, first charging at a constant current to 4.5V, then charging at a constant voltage to a cut-off current of 0.05C, and finally discharging at a constant current. The discharge capacity at the first cycle and the discharge capacity at the 100th cycle are measured respectively, and the capacity retention rate is calculated. Calculation formula: Capacity retention rate after 100 cycles (%)=Discharge capacity at the 100th cycle ÷ Discharge capacity at the first cycle × 100%. The specific capacity of the material is obtained, and the electrochemical performance after product testing is shown in Table 1.

[0068] Table 1: Product electrochemical test results

[0069]

[0070] It can be seen from the electrical performance test results in Table 1 that the capacitance of Examples 1-3 is higher than that of Comparative Examples 1-2, especially under high rate conditions. It is obvious that Examples 1-3 are conducive to the synthesis of small particles, and thus also conducive to the release of capacitance.

Claims

1. A method for preparing a lithium iron manganese phosphate positive electrode material, comprising mixing a lithium source, a phosphorus source, a carbon source, an iron source and a manganese source, and then granulating and sintering the mixture, wherein the method comprises: The iron source and manganese source are derived from manganese ferrocyanide, wherein the chemical formula of manganese ferrocyanide is Mn3[Fe(CN)6]2, and the chemical formula of lithium manganese iron phosphate is LiMn 0.6 Fe 0.4 PO4.

2. The method for preparing lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The manganese ferrocyanide is a manganese ferrocyanide solution with a mass concentration of 30% to 40%, and the solvent is deionized water.

3. The method for preparing lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that The lithium source and phosphorus source are selected from lithium dihydrogen phosphate, or the lithium source and phosphorus source are selected from a mixture of lithium carbonate and ammonium dihydrogen phosphate.

4. The method for preparing lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that The carbon source is selected from one or more of acetylene black, carbon nanotubes and carbon black.

5. The method for preparing lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that The carbon source is selected from one or more of sucrose, glucose, citric acid and ascorbic acid.

6. The method for preparing lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that Prepare as follows: S1: using deionized water as a solvent and mixing it with manganese ferrocyanide to obtain a mixture I, wherein the mixture I is a manganese ferrocyanide solution with a mass concentration of 30% to 40%; S2: adding a lithium source, a phosphorus source and a carbon source to the mixture I to obtain a mixture II, wherein the ratio of lithium atoms to the total atoms of iron and manganese in the mixture II is 1.03-1.05:1, the ratio of phosphorus to lithium is 1:1, and the amount of carbon source added is 8-10% of the total mass of lithium iron manganese phosphate; S3: Granulating the mixture II to obtain spray-dried granulated particles, wherein the drying air inlet temperature is 240-260° C., the air outlet temperature is 70-90° C., and the particle size of the granulated particles is 10-30 μm; S4: Sintering the particles at high temperature to obtain LiMn 0.6 Fe 0.4 PO4, wherein the sintering temperature is 720-760°C and the holding time is 8-12 hours; S5: The sintered material is subjected to air flow pulverization to obtain the finished product LiMn 0.6 Fe 0.4 PO4 positive electrode material, wherein D50 is 2-5 μm, wherein the crushing parameters are gas source pressure of 0.55-0.65 MPa, feeding frequency of 36-46 Hz, and classifying wheel frequency of 42-45 Hz.

Citation Information

Patent Citations

  • Preparation method of carbon-coated lithium iron manganese phosphate positive electrode material

    CN111900344A

  • Lithium manganese iron phosphate composite material as well as preparation method and application thereof

    CN116692814A

  • Lithium iron manganese phosphate cathode material and preparation method thereof

    CN111564622A

  • Composite positive electrode material and preparation method and application thereof

    CN115832256A